2011
DOI: 10.1080/09540121.2011.554517
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of staff and workload profiles in retaining patients on antiretroviral therapy in KwaZulu-Natal, South Africa

Abstract: The results could be used to estimate the human resources needed for a sustainable scaling up of ART in KZN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Out of 574 abstracts retrieved, 150 full-text studies were assessed for eligibility; of those, 29 were included in analysis: 26 on ART (23 on adult ART, two on adult and pediatric ART [21, 22] , and one on pediatric ART only) [23] (tables I, II and III). Table IV provides results for the base case and the sensitivity analysis for ART unit costs, and fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of 574 abstracts retrieved, 150 full-text studies were assessed for eligibility; of those, 29 were included in analysis: 26 on ART (23 on adult ART, two on adult and pediatric ART [21, 22] , and one on pediatric ART only) [23] (tables I, II and III). Table IV provides results for the base case and the sensitivity analysis for ART unit costs, and fig.…”
Section: Resultsmentioning
confidence: 99%
“…[22, 2428] Studies for lower-middle-income countries (LMIC) were found for India [29, 30] , Lesotho [18] , Morocco [31] , Nigeria [32, 33] , and Thailand [34] ; the median cost of ART was $932 (mean $1,246, range $156 to $3,904) (tables II & IV). In upper-middle-income countries (UMIC), Brazil [23, 35] , Mexico [3638] and South Africa [21, 3945] the median ART cost was $1,454 (mean $2,783; range $1,230 to $5,667) (tables III & IV). …”
Section: Resultsmentioning
confidence: 99%
“…Of those examining provider or facility interventions [13], we found only one that evaluated an adherence improvement strategy in a low-income country setting [14]. In Nicaragua, only one study has examined economic issues of HIV care: a cost analysis of centralized viral load testing [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research 4,5 (Garrido: submitted for publication) shows that contact with TB patients (in the same household, neighborhood, workplace, or hospital) is an important risk factor that requires investigation for MDR-TB at the beginning of treatment. Therefore, sputum culture, strain identification, and sensitivity testing should all be included in the list of priorities of the National Tuberculosis Control Program in order to break the chain of transmission 10 .…”
Section: Case Reportmentioning
confidence: 99%
“…In the transmission of resistant strains, the greatest individual risk factor is sharing living quarters with individuals who have defaulted on their TB treatment or are relapse cases 4,5 . The appearance of patients with first-line MDR-TB leads to the use of alternative medications, often at higher costs, longer treatment periods, and greater clinical complexity due to the fact that these drugs are injectable and tend to lead to more side effects 6,7 .…”
mentioning
confidence: 99%